Prenatal follow-up of Haitian and Brazilian women in Mato Grosso - Delma Riane Rebouças Batista; Silvia Angela Gugelmin; Ana Paula Muraro
Abstract Objectives: to analyze the prenatal follow-up performed by pregnant women in Haiti and Brazil in the state of Mato Grosso. Methods: a cross-sectional study of secondary database, with analysis of SINASC birth records in Mato Grosso between 2013 and 2015, of Brazilian children, born from both Brazilian and Haitian mothers. Variables related to the identification of the newborn and the woman, maternal data on gestational history, including information on prenatal follow-up of the last gestation were evaluated, besides the birth characteristics. Results: 167,820 live births were registered in the state in the period, of which 139 (0.08%) were children of Haitian women. Haitian mothers were older, however with lower schooling when compared to Brazilian mothers. The proportion of mothers of Haitian nationality who had at least 6 prenatal consultations was lower, and the proportion of vaginal births was higher, when compared to Brazilian women. The prevalence of low birth weight among live births of Haitian mothers was also higher. Conclusions: the results of this study point to the need to understand these differences, since some indicators have distanced from those advocated by WHO. These findings may contribute to the public policies development aimed at this population.